BUREAUCRATIC EFFICIENCY ISSUANCE OF HALAL CERTIFICATES FOR MICRO AND SMALL BUSINESSMEN - rosidah, zaidah nur (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The obligation to be halal certified for micro and small business actors must be implemented no later than October 17 2026, but to date there are still many micro and small business actors who do not have a halal certificate. This research aims to evaluate the bureaucracy of issuing halal certificates for micro and small businesses. As well as providing recommendations so that the bureaucracy of issuing halal certificates for micro and small businesses becomes efficient.The research method used in this research uses a socio legal study approach. Primary data collection was carried out by conducting interviews with several micro and small business actors, the halal task force of the ministry of religion and the cooperative, SME and industry services. Meanwhile, secondary data was collected through library studies of primary and secondary legal materials. To obtain answers to deductive syllogism research problems.The results of the research obtained several conclusions, namely first, the obligation to be certified halal for micro and small business actors is still not implemented well, there are still many micro and small business actors who do not have a halal certificate. The influencing factor is a lack of knowledge because the outreach carried out by the halal task force and the SME and industrial cooperatives service has not reached all micro and small business actors. Second, the bureaucracy of issuing halal certificates for micro and small businesses is inefficient regarding time and energy. The time required to issue a halal certificate is an average of 2 to 3 months compared to the 12 working days required for self-declaration and the regular 21 working days. The fee for issuing a halal certificate is free if you apply through the self-declare mechanism, and is charged if you go through the regular route. The institutions involved in issuing halal certificates are MUI, LPH, and BPJPH. However, MUI involvement is still with the Central MUI.